2002
DOI: 10.2514/2.1533
|View full text |Cite
|
Sign up to set email alerts
|

Forward-Running Detonation Drivers for High-Enthalpy Shock Tunnels

Abstract: To improve the quality of driving ows generated with detonation-driven shock tunnels operated in the forwardrunning mode, various detonation drivers with specially designed sections were examined. Four con gurations of the specially designed section, three with different converging angles and one with a cavity ring, were simulated by solving the Euler equations implemented with a pseudo kinetic reaction model. From the rst three cases, it is observed that the re ection of detonation fronts at the converging wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This partial reflection serves to trap highpressure gas in a fashion similar to a reflected shock tunnel and serves to alleviate attenuation from the Taylor rarefaction, thereby prolonging the duration of uniform flow within the driven tube. Jiang et al (1999Jiang et al ( , 2002 have further studied this technique of increasing the run time and flow uniformity through the use of "cavity rings." Finally, at the end of a successful run, the end diaphragm is blown away and the entire shock tube is vented.…”
Section: Facility Descriptionmentioning
confidence: 99%
“…This partial reflection serves to trap highpressure gas in a fashion similar to a reflected shock tunnel and serves to alleviate attenuation from the Taylor rarefaction, thereby prolonging the duration of uniform flow within the driven tube. Jiang et al (1999Jiang et al ( , 2002 have further studied this technique of increasing the run time and flow uniformity through the use of "cavity rings." Finally, at the end of a successful run, the end diaphragm is blown away and the entire shock tube is vented.…”
Section: Facility Descriptionmentioning
confidence: 99%
“…It is found that the flow field behind a detonation wave generated by the tube with a cavity ring is more uniform than that by the tube with a 30 • or 45 • converging section. In order to verify the results, a forward-detonation driven shock tube has been manufactured in LHD [18]. The detonation driver consists of a large tube (3.87 m long and 90 mm in Dia.…”
Section: Inserting a Cavity Ringmentioning
confidence: 99%
“…The data deduction carried out only by pitot pressure measurements is not enough to validate the real flow condition, other measures such as heat-flux measurements and spectrum analysis are necessary to fully detect the flow characteristics, which were already reported in [7]. The amount of transducers consumed during the test is high, few are working normally at last.…”
Section: Results Of Downstream Operation Modementioning
confidence: 99%
“…However, due to the Taylor rarefaction wave which follows the detonation front, the primary shock wave is attenuated. Jiang et al [7] and Zhao et al [10] developed some ways to solve these problems. Another problem to solve then was to burst the primary metal diaphragms, which produced fragments at the moment of rupture.…”
Section: Introductionmentioning
confidence: 99%